CONSONANTAL ORGANIZATION IN ENGLISH POETIC DISCOURSE: TOPOLOGICAL PERSPECTIVE - Natalia Neborsina (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The aesthetic reflection of the world in language finds its expression in the oldest, phonetic aspect of the word's meaning. Phonetic timbre is the distinctive quality in the sounds of words. A marked consistency of texture in poetic discourse is achieved by alliteration. There is a growing interest in its aesthetic measure. The aim of this article is to suggest, following G. Mazzola, a conceptual framework for consonantal analysis of poems in terms of the category of topological spaces. The topological space of the line is viewed as made of phonetic toposes. They include a consonant sound and its morphism. A consonant sound carries substance and is called "denotator". The conceptual form of denotator consists of Name, Type, and Coordinator. The name of the consonant represents the phonetic theme: the n phonetic theme embraces high timbre consonants, while the m phonetic theme includes low timbre consonants. Two types of consonance are singled out - complete consonance and incomplete consonance. The results of the analysis of poetic discourse show that complete consonance coordination has two forms: simple morphism and compound morphism. In case of incomplete consonance the morphism is intensified or lax. Phonetic topology may prove to be an effective mechanism in the study of "orchestration of voice" in poetic discourse as a socio-cultural phenomenon.